Pengaruh Kinerja Keuangan dan Kinerja Olahraga Terhadap Harga Saham Klub Sepakbola - Fany Dwi Nurcahyani; Loggar Bhilawa (Universitas Kristen Maranatha, 2021)
This study measures whether the financial and sports performance of a football club has an effect on stock prices. Financial performance can be measured through several methods, one of which is the measurement of financial performance using ratio analysis. This study observes the financial performance of football clubs in Europe who also sell their shares in capital markets such as the London Stock Exchange, BorsaItaliana, and Xetra. Research methods with quantitative approaches are used in this study. Sports performance is measured by the number of wins, losses and match series. There were 18 soccer clubs observed in this study. A simple linear regression analysis model is used to see the effect of financial and sports performance on soccer club stock prices. We find it unique in this study that the financial performance of football has a more substantial effect than sports performance which does not have a substantial effect on the stock price of football clubs. Keywords: Capital Market, Financial Performance, Football Club,and Stock Prices